Hubungan Perbandingan Sosial Upward dengan Kecemasan Finansial pada Gen Z Pengguna TikTok - Natalie Natalie; Untung Subroto (Lembaga Yasin AlSys, 2026)
TikTok use that highlights idealized lifestyles and financial achievements often triggers upward social comparison, which may increase financial anxiety among young users. This study aimed to test the relationship between upward social comparison on TikTok and financial anxiety among Gen Z. The study involved 206 respondents aged 18–27 years who were active TikTok users. Data were collected via Google Forms using the Iowa-Netherlands Comparison Orientation Measure (INCOM) to assess social comparison orientation and the Financial Anxiety Scale (FAS) to evaluate levels of financial anxiety. The main findings showed a positive and significant relationship between upward social comparison and financial anxiety (r = 0.684; p = 0.000), indicating that the greater an individual’s tendency to compare themselves with other users perceived as superior, the higher the financial anxiety they experience. These results confirm that social comparison dynamics on TikTok constitute an important psychological factor that should be considered in prevention and intervention efforts targeting financial anxiety among young people.